2018
DOI: 10.2134/agronj2017.12.0684
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Agronomic Practices to Maximize Feed Barley Yield, Quality, and Standability in Alberta, Canada. II. Responses to Supplemental Post‐Emergence Nitrogen

Abstract: Agronomic solutions such as supplemental post‐emergence N may increase yield of feed‐barley grain. Grain yield, grain N yield, and grain protein generally increased as post‐emergence N rate increased. Largest grain yield increases occurred in environments with >300 mm of growing season precipitation. Yields decreased when N was applied as urea ammonium nitrate in hot and low‐precipitation conditions. There were no adverse negative effects to maturity, lodging, or grain quality in ‘Amisk’ feed barley. Small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…The geo-spatial variations of modeled dryland barley grain yields and N uptake across different soil groups and climates in Alberta during 2011-2015 matched reasonably well against observed variations in barley yields and N uptake reported across Alberta (Figures 6-8) (McKenzie et al, 2004;Anbessa and Juskiw, 2012;Perrott, 2016). However, modeled barley yields FIGURE 6 | (A) Spatial distribution of observed and modeled dryland or rainfed barley grain yields across Alberta's agricultural areas averaged over the simulation period (2011-2015).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The geo-spatial variations of modeled dryland barley grain yields and N uptake across different soil groups and climates in Alberta during 2011-2015 matched reasonably well against observed variations in barley yields and N uptake reported across Alberta (Figures 6-8) (McKenzie et al, 2004;Anbessa and Juskiw, 2012;Perrott, 2016). However, modeled barley yields FIGURE 6 | (A) Spatial distribution of observed and modeled dryland or rainfed barley grain yields across Alberta's agricultural areas averaged over the simulation period (2011-2015).…”
Section: Discussionsupporting
confidence: 68%
“…These phenomena were not accounted for in these simulations since these simulations included only welldrained, mid-slope landforms, which tend to be higher yielding. Although the modeled dryland barley grain yields were larger than the AFSC data, the modeled grain yields and grain N uptake were well within the ranges of long-term experimental data on barley grain yields (i.e., 4,300-6,900 kg ha −1 year −1 ) and N uptake (i.e., 81-131 kg N ha −1 year −1 ) across brown, dark brown, black, and gray soils of southern and central Alberta (Figures 7, 8) (McKenzie et al, 2004;Anbessa and Juskiw, 2012;Perrott, 2016).…”
Section: Discussionsupporting
confidence: 63%
“…Other studies also observed minimal responses to some stem structures. For example, application of Manipulator also improved the grain yield and plant structure without notable changes to plant height and lodging in barley ( Hordeum vulgare L.) (Perrott et al., 2018). For winter cereals and barley, uptake of a PGR seemingly initiates partition changes in carbon allocation to reproductive parts of the plant over the stem wall.…”
Section: Resultsmentioning
confidence: 99%
“…However, the conserved N translated into an increase in yield, N uptake, and NUE in CSL but not in PCL. The lack or inconsistency of the effect of NBPT (with or without NI) on the yield of small grains is common on the Canadian prairie, as reported in the previous studies of Grant (2014), McKenzie et al (2010), and Perrott et al (2018, who found no effect of NBPT on grain yield from surface-applied urea. The lack of any effect of NBPT on the yield and N uptake of small grains is because the N conserved with the use of NBPT is relatively small compared with the influence of applied N fertilizers and soil N (residual nitrate + mineralization) on the yield of wheat and canola.…”
Section: Discussionmentioning
confidence: 86%
“…(2010), and Perrott et al. (2018), who found no effect of NBPT on grain yield from surface‐applied urea. The lack of any effect of NBPT on the yield and N uptake of small grains is because the N conserved with the use of NBPT is relatively small compared with the influence of applied N fertilizers and soil N (residual nitrate + mineralization) on the yield of wheat and canola.…”
Section: Discussionmentioning
confidence: 94%